Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.3758/bf03193637
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements during search and detection in comparative visual search

Abstract: Motivated by the fact that previous visual memory paradigms have imposed encoding and retrieval constraints, the present article presents two experiments that address how observers allocate eye movements in memory and comparison processes in the absence of constraints. A comparative visual search design (Pomplun, Sichelschmidt, et al., 2001) was utilized in which observers searched for a difference between two images presented side by side. Robust time course effects were obtained, whereby search was character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 45 publications
(77 reference statements)
1
13
0
2
Order By: Relevance
“…Reduced fixation to eccentric AOIs could be an explanation as well, but the results of other studies cast doubt on such an eccentricity effect. For example, Galpin and Underwood (2005), in a comparative visual search study, had their observers make 16.5º eye movements without the possibility to move their heads, and apparently without any difficulty on their part. In the present experiment, the visual angle between the left eyes of both faces was typically about 14º.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced fixation to eccentric AOIs could be an explanation as well, but the results of other studies cast doubt on such an eccentricity effect. For example, Galpin and Underwood (2005), in a comparative visual search study, had their observers make 16.5º eye movements without the possibility to move their heads, and apparently without any difficulty on their part. In the present experiment, the visual angle between the left eyes of both faces was typically about 14º.…”
Section: Resultsmentioning
confidence: 99%
“…in comparative visual search tasks (Galpin & Underwood, 2005), or they could compare the faces as a "whole." The latter would be indicated, for example, by more extensive scanning patterns on each face before comparison with the other face, and/or by relatively few comparison saccades between faces.…”
mentioning
confidence: 99%
“…This is possible because evidence shows that eye fixations pick up information as and when it is used for task completion (Hayhoe and Ballard, 2005). Within cognitive science many studies have applied eye-tracking to understand strategy across a range of tasks, including mental rotation (Just and Carpenter, 1976), visual search (Zelinsky et al, 1997), and comparative visual search (Galpin and Underwood, 2005). However, the focus of this work has been on general patterns in strategy aggregated across participants, rather than individual differences.…”
mentioning
confidence: 99%
“…However, the focus of this work has been on general patterns in strategy aggregated across participants, rather than individual differences. For example, Galpin and Underwood (2005) demonstrated that observers searched for differences between two pictures by making frequent point-by-point comparisons until detecting a difference, upon which the focus of attention narrowed and fixation durations increased. However, no attempt was made to assess how this strategy varied across participants.…”
mentioning
confidence: 99%
“…Isto sugere que os participantes com menores pontuações no MMSE apresentam maior NV devido a um potencial fraco uso da memória de trabalho. Estes dados reforçam a ideia de que, no grupo com pontuação inferior no MMSE, a manutenção e processamento da informação visual apresenta uma maior deterioração ao longo do tempo, existindo a necessidade de realizar sacadas alternadas entre AdI para manter o traço mnésico ativo (Galpin & Underwood, 2005).…”
Section: Discussionunclassified